Cellular and biochemical changes associated with induction of the defense system in Berangan (AAA) banana / Kelvin Kiran Anthony - Kelvin , Kiran Anthony (2018)
Fusarium infection of bananas is a global problem that threatens the production of bananas. This thesis looks at the effects of the infection upon the Reactive Oxygen Species (ROS) system as well as the induced antioxidant properties and antifungal protein activities in the Berangan fruits at Stage I, V and in infected fruits. ROS assays were divided into two classes: ROS assays and ROS-scavenging assays. Of the ROS assays, lipoxygenase was observed to be higher in the infected samples while peroxidase and polyphenol oxidase were significantly higher in infected fruit samples. Induction of ROS is important for the hypersensitive response to function properly. The ROS-scavenging enzymes, namely ascorbate peroxidase, guaiacol peroxidase and superoxide dismutase, exhibited higher levels in the infected tissue. This is most likely in order to counter the build-up of the ROS enzymes and to prevent further cell death. The increase in ROS-scavenging assays also correlates with higher antioxidant properties as antioxidants play a critical role in regulating the hypersensitive response free radicals. Furthermore, antifungal protein properties were observed to be higher in infected fruit samples.